GAPS BETWEEN EXPERT’S AND STUDENT’S EXPOSITION TEXTS BASED ON SYSTEMIC FUNCTIONAL LINGUISTICS (SFL): IMPLICATION FOR TEACHERS - Sinta Dewi (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The lack of students’ ability to compose expository text is still found in many mainstream classrooms. The inability may be caused by many factors such as the complexity of the text itself, the texts in the textbook which are often not representative enough to be the model texts, and teachers’ lack of awareness of teaching genre. This study intends to investigate the gaps between the model (expert) and students’ texts at genre level and register level based on SFL perspectives. To serve the aims, this study employed case study design in attempt to get clear description from the case investigated. The data gathered from the analysis focusing on genre level and register level were presented in narrative form and interpreted descriptively. The finding showed that at genre level the student’s text did not include the restatement of thesis which is different from the expert’s text. Meanwhile, at register level, the student’s text appears to have lack of cohesive devices and other mode choices (e.g. lack of marked theme, connectives) which lead into the lack of texture of the text. Careful design of activities in each curriculum cycle and explicit teaching of both schematic structures and registers of expository are the implications suggested by this study.